2005
DOI: 10.1002/ijc.21658
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL‐induced cell death cooperates with IFN‐γ activation in the graft‐versus‐tumor effect against colon tumors

Abstract: The graft-versus-tumor (GVT) effect that occurs following allogeneic bone marrow transplantation (BMT) and donor lymphocyte infusion (DLI) is currently being subjected to intensive investigation because of clinical evidence for GVT efficacy against leukemia. In this report, we investigate the efficacy and molecular mechanisms of GVT against solid tumors, using a modification of the mouse parent-to-F1 BMT model. Mouse Colon26 cells in which tumor necrosis factor related apoptosis-inducing ligand (TRAIL) recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
5
1
Order By: Relevance
“…IFN-γ has also been shown to enhance apoptosis with other cytokines or death-related receptors [19], [20], [21]. In our study of the hepatoma ML-1 4a cell line, we found neither any caspase-3 activation, nor any characteristics of apoptosis within 24 hours post IFN-γ treatment.…”
Section: Discussioncontrasting
confidence: 74%
“…IFN-γ has also been shown to enhance apoptosis with other cytokines or death-related receptors [19], [20], [21]. In our study of the hepatoma ML-1 4a cell line, we found neither any caspase-3 activation, nor any characteristics of apoptosis within 24 hours post IFN-γ treatment.…”
Section: Discussioncontrasting
confidence: 74%
“…It will be interesting to further analyze whether the anti-metastatic effect of endogenous TRAIL signaling via TRAIL-R is particularly important for lymph node metastases. This could be facilitated through increased TRAIL expression in lymphatic cells or increased sensitization of tumor cells to TRAIL in the lymphatic system, for example through cytokines such as γIFN (14). …”
Section: Trail-r As a Metastasis Suppressormentioning
confidence: 99%
“…These cells produced IFN-γ and mediated TRAIL-dependent lysis of tumor cells [18]. Two separate studies demonstrated that TRAIL and IFN-γ cooperate in anti-tumor effects in vivo [19,20]. Upon engagement of the T-cell receptor, triggering of the TRAIL signaling pathway results in an augmented proliferation and IFN-γ production in antigen-specific T cells [21].…”
mentioning
confidence: 99%